Environmental Crisis in Urban Areas in J. G. Ballard’s Short Stories - Barış Ağır (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
This study mainly applies Lawrence Buell’s environmental criticism to study the urban environment in J. G. Ballard’s short stories from two aspects: the environmental problems and humankind’s failed resistances to them. Through studying these aspects, the paper discloses Ballard’s reproof of the industrial society’s disrespect towards nature and his ecological concerns over the development of both the environment and the human being. The paper will study the status of the urban environment from two angles: the absence of green landscape and the prevalence of pollution. The paper will interpret how the characters attempt to resist the predicaments but end up in failures. Though their attempts do not succeed, seeing from Buell’s theory, this kind of pessimistic extremity in Ballard’s imagination could also reflect his determination of arousing readers’ awe in facing nature and their consciousness of environmental protection. By stressing the environmental predicaments, humankind’s crises under the predicaments, and the futile resistances, Ballard’s urban short stories express a profound ecological concern with the urban environment and humanity’s existential status.